2012
DOI: 10.5688/ajpe767126
|View full text |Cite
|
Sign up to set email alerts
|

Entry Characteristics and Academic Performance of Students in a Master of Pharmacy Degree Program in the United Kingdom

Abstract: Objective. To evaluate the characteristics of a cohort of master of pharmacy (MPharm) students upon entry into the program and examine associations between entry qualifications, type of secondary school attended, socioeconomic status, age, and academic performance in the MPharm program. Methods. A retrospective cohort analysis was conducted of student data for graduates of the Aston University MPharm program during the 5-year period 2005-2006 through 2009-2010 (n5644). Results. MPharm entrants were disproporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…As it has been identified in detail concerning the entry characteristics and their influence on academic performance, the study showed that WASSCE as an entry characteristic had a significant positive association with competence and total performance of the students. This corroborates some earlier studies [11][12][13][14][15]26], which found that students' entry qualifications into universities contributed significantly to their academic performance. This suggests that depending on the WASSCE qualification of an individual in the university, their academic success in terms of competence can be gauged and thus consistent with the studies of Alhajraf and Alasfour [13], which found that students' entry qualifications into the tertiary level predict a level of academic achievement at university.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As it has been identified in detail concerning the entry characteristics and their influence on academic performance, the study showed that WASSCE as an entry characteristic had a significant positive association with competence and total performance of the students. This corroborates some earlier studies [11][12][13][14][15]26], which found that students' entry qualifications into universities contributed significantly to their academic performance. This suggests that depending on the WASSCE qualification of an individual in the university, their academic success in terms of competence can be gauged and thus consistent with the studies of Alhajraf and Alasfour [13], which found that students' entry qualifications into the tertiary level predict a level of academic achievement at university.…”
Section: Discussionsupporting
confidence: 92%
“…Empirically, some studies have discovered that the strongest predictor of university achievement was students' entry qualifications to gain admission [11][12][13]. In support of the argument, Wadda et al [14] and Bush [15] stressed a strong correlation between entry characteristics and academic achievement. However, there is credible contradictory evidence [16] that there is no connection between students' entry qualifications and subsequent academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Science subjects were highlighted as prerequisites in all cases, with chemistry being stipulated by all and a mix of mathematics/biology/ physics by most. [16][17][18] English was also an important prerequisite for all, although the level of evidence required varied, with several schools stipulating grades from high school year 11, or via standardized tests of English as a second language such as the International English Language Testing System (IELTS). While adequate preparation in science subjects is important for prospective pharmacy students, and they need to be mathematically and scientifically literate, the heavy emphasis on science Most schools required a personal profile/statement.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] However, as argued by Svennson et al, "there appears to be little research on how good these measures are at predicting applicants' future leadership potential or the likelihood of becoming change agents for the profession." 14 Additional selection processes are used by schools, such as interviews, psychometric tests, candidate profiles, and self-reflective statements, but these processes vary, even within the same country.…”
Section: Introductionmentioning
confidence: 99%
“…Across the United States of America (USA), universities continue to study admission criteria to improve selection processes and support students toward academic success (Stuenkel, 2006). According to Bush (2012), a study of students from United Kingdom (UK) higher education institutions indicated that prior achievements at the Advanced (A) Level were among the most important predictors of university academic performance. However, universities' use of A-level performance as the primary criterion for admission to undergraduate degree programs has been subject to criticism.…”
Section: Introductionmentioning
confidence: 99%